VD_FINDINFO HC / 2017 / 1161 vom 16. November 2017 - VD Tribunal cantonal (2017)
PROTECTION DE L'UNION CONJUGALE, RÉTROACTIVITÉ, OBLIGATION D'ENTRETIEN | 173 al. 3 CC, 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH)